The influence of organization culture on teacher performance of elementary school - Ayu Tahnia; Happy Fitria; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to discover the significant influence of Organization Culture on teacher performance in cluster 1 Rambutan Subdistrict, Banyuasin Regency . This research uses quantitative methods. Data collection techniques using questionnaires and documentation. The data was analyzed using multiple linear regression formulas.The results of this study show that there is a significant influence of Organization Culture on teacher performance of elementary school with a t count value of 4,182 and t table of 1,998 where t count > t table then Ha2 received. The conclusion of this research is that good organization culture where they would actualized teacher performance.